Thermodynamic stability, magnetism and half metallicity of Mn2CoAl/GaAs(0 0 1) interface. (16th June 2015) - Feng, Yu; Zhou, Ting; Chen, Xiaorui; Yuan, Hongkuan; Chen, Hong
Abstract: Interface properties of the heterojunction which is composed of the inverse Heusler alloy Mn CoAl and semiconductor GaAs are investigated by employing the first-principles density functional simulations. Two kinds of interface structures, namely the top-type and bridge-type structure by connecting termination of nine Mn CoAl layers to the top of the As-terminated GaAs layer and bridge site between interface As atoms are respectively built. Our calculations reveal that, as for the structure with the same interface atoms, different atoms sitting directly on top of the interface As atom will lead to different interface magnetism and electronic structures. The calculated phase diagram reveals that the top-type structure including natural MnCo or MnAl termination is stable only when the interface Mn or interface Al atom directly locates on top of the As atom. Besides, bridge-type and top-type structures containing a pure Mn interface are always thermodynamically accessible regardless of values of the chemical potential of Mn and Co. The atom-resolved spin magnetic moments of most interface magnetic atoms are enhanced due to the rehybridization caused by symmetry breaking at the interface. Further analyses on electronic structures indicate that, owing to the interface effect, the interface half metallicity of all structures are completely destroyed. However, the top-type structure with MnAl termination where the interface Al atom directly sits on top of the As atom preserves the highest interface spin polarization of 80%, indicating that it has more advantages in spintronics application than other atomic terminations.